HUBUNGAN MOTIVASI TERHADAP KINERJA PETUGAS KESEHATAN: STUDI KASUS PUSKESMAS KALIBARUKULON, BANYUWANGI - Eka Suci Daniyanti; Agus Putra Murdani; Siti Rubiyanti (Fakultas Kesehatan Masyarakat, Universitas Jember, 2018)
Work motivation is one of the important aspects in the human resources management, so that in the implementation of the organization can achieve useful and effective goals and objectives. The performance of health workers is the result of the effort to create the quality of service will certainly create userssatisfaction. Based on the work area and the lack of health personnel, Kalibarukulon Public Health Center needs to be observed in the relationship between motivation and performance. This research was conducted at Puskesmas Kalibaru Kulon, Kalibaru Subdistrict, Banyuwangi Regency. The study was conducted during September 2016. Kalibaru Kulon. This study uses questionnaire type checklist. Quiz results show that 63.9% of respondents are female, while 36.1% are male. As many as 50% of respondents entered the age range 30-40 years, 33.3% were> 40 years old, and 16.7% were <30 years old. In addition, the status of employment shows that most (58.3%) are civil servants / permanent, and 22.2% are contract workers (PTT) and 19.5% are freelancers (THL). The results of the questionnaire also showed the work motivation on the respondents, that is 66.7% have the motivation of good work and 13.9% have less motivation. A total of 72.2% of respondents stated to have a good performance